Immuno-dominant dengue NS1 peptides as antigens for production of monoclonal antibodies - Munasinghe, Erandi; Athapaththu, Maheshi; Abeyewickreme, Wimaladharma (Frontiers in Molecular Biosciences, 2022)
Synthetic peptides have recently become common as antigens for antibody production. Peptides are a short chain of amino acids that can be used to elicit an immune response. Immunogenicity of the peptide antigens vary depending on the length, charge, solubility and amino acids contained in the peptide sequence. Dengue NS1 protein is an important target antigen in the early detection of dengue infection. In this study, peptides corresponding to a highly conserved region from the dengue NS1 region were designed and synthesized. Balb/C mice were immunized against each peptide and extracted spleen cells from immunized mice were fused with NSO murine myeloma cells. Hybridoma clones obtained from fusions were tested against peptides using ELISA. Out of 1830 growing clones, 28 clones produced antibodies reacting with dengue NS1 peptides. A purified monoclonal antibody reacting with all four peptides was tested for reactivity with dengue NS1 native protein using dengue-confirmed serum and urine samples. The monoclonal antibody shows significant reactivity with both serum and urine. The findings of the current research can be used to detect dengue infection using urine which ultimately results in the prevention of dengue epidemics through painless diagnosis, following treatment, and patient management to safeguard human and economic wellness.